Análise dos fatores motivacionais dos corretores de imóveis da cidade de São Paulo - Gines Júnior, Clovis Soler (2008)
The routine work of the realtor is associated with marketing a tangible product (building) or intangible (building the plant). We can find extensive information on the sector of construction, real estate, investments in industry and other important information, but quantitative data on these professionals are hard to find. The realtor holds its activity so unattended. It may or may not be associated with a building, but without employment bonds with the same, a trait that can be observed from the origin of the profession. When coupled with a property is part of the sector and its operational responsibilities meet customers and sell real estate, high-standard, medium standard or associations, residential or commercial, rural or urban, with options to buy, sell, lease or exchange. Based on this profile, this study sought to identify the factors that motivate the Real Estate to follow this profession. The goal of this dissertation was to conduct an exploratory study on the profession of real estate broker. The methodological procedure, then was an exploratory study used a quantitative model with a structured questionnaire. The conclusion of this study indicate that: working conditions, the policies of the administration building and the lack of recognition in the organizational environment were the main items of dissatisfaction. However, it was possible to observe the importance of salary or remuneration from the sales are to people, whereas those who are satisfied with their earnings have not dissatisfied with working conditions, the policies of the administration building or the lack of recognition in the organizational environment, ie, the research reveals the natural selection of characteristics that predispose self